NLRP3 Deficiency Reduces Macrophage Interleukin-10 Production and Enhances the Susceptibility to Doxorubicin-induced Cardiotoxicity - Motoi Kobayashi; Fumitake Usui; Tadayoshi Karasawa; Akira Kawashima; Hiroaki Kimura; Yoshiko Mizushina; Koumei Shirasuna; Hiroaki Mizukami; Tadashi Kasahara; Naoyuki Hasebe; Masafumi Takahashi (2016)
NLRP3 inflammasomes recognize non-microbial danger signals and induce release of proinflammatory cytokine interleukin (IL)-1β, leading to sterile inflammation in cardiovascular disease. Because sterile inflammation is involved in doxorubicin (Dox)-induced cardiotoxicity, we investigated the role of NLRP3 inflammasomes in Dox-induced cardiotoxicity. Cardiac dysfunction and injury were induced by low-dose Dox (15 mg/kg) administration in NLRP3-deficient (NLRP3(-/-)) mice but not in wild-type (WT) and IL-1β(-/-) mice, indicating that NLRP3 deficiency enhanced the susceptibility to Dox-induced cardiotoxicity independent of IL-1β. Although the hearts of WT and NLRP3(-/-) mice showed no significant difference in inflammatory cell infiltration, macrophages were the predominant inflammatory cells in the hearts, and cardiac IL-10 production was decreased in Dox-treated NLRP3(-/-) mice. Bone marrow transplantation experiments showed that bone marrow-derived cells contributed to the exacerbation of Dox-induced cardiotoxicity in NLRP3(-/-) mice. In vitro experiments revealed that NLRP3 deficiency decreased IL-10 production in macrophages. Furthermore, adeno-associated virus-mediated IL-10 overexpression restored the exacerbation of cardiotoxicity in the NLRP3(-/-) mice. These results demonstrated that NLRP3 regulates macrophage IL-10 production and contributes to the pathophysiology of Dox-induced cardiotoxicity, which is independent of IL-1β. Our findings identify a novel role of NLRP3 and provided new insights into the mechanisms underlying Dox-induced cardiotoxicity.